High Inflation and Real Wages - Braumann, Benedikt (Washington, D.C. : International Monetary Fund, 2001)
Empirical data show that real wages fall sharply during periods of high inflation. This paper suggests a simple general equilibrium explanation, without relying on nominal rigidities. It presents an intertemporal two-sector model with a cash-in-advance constraint. In this setting, inflation reduces real wages through (1) a decline of the capital stock, and (2) a shift in relative prices. The two effects are additive and make the decline in real wages exceed the decline in per-capita GDP. This mechanism may contribute to rising poverty during periods of high inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet